2021
DOI: 10.1038/s41394-020-00377-z
|View full text |Cite
|
Sign up to set email alerts
|

Spinal cord injuries and bowel stomas: timing and satisfaction with stoma formation and alterations in quality of life

Abstract: Study design Cross-sectional study. Objectives Neurogenic bowel dysfunction (NBD) is frequent among individuals with spinal cord injury (SCI) and is often difficult to treat. A bowel stoma is considered the last-resort treatment option for individuals with SCI and severe NBD. This study aims to explore whether individuals are satisfied with their bowel stoma and how they feel about the timing of stoma formation. Furthermore, we want to explore side effects addressing di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
0
0
Order By: Relevance
“…Rectal discharge may also still occur, even in the presence of a stoma [2]. Several studies have investigated the results of stoma formation in the SCI population and concluded that stoma in general is well tolerated and accepted, increases independence and decreases time spent on bowel management, as well as improves quality of life [55][56][57][58]. Most patients in these studies had received a colostomy; however, some had an ileostomy and a few ended up with both eventually, primarily due to complications.…”
Section: Stomamentioning
confidence: 99%
See 1 more Smart Citation
“…Rectal discharge may also still occur, even in the presence of a stoma [2]. Several studies have investigated the results of stoma formation in the SCI population and concluded that stoma in general is well tolerated and accepted, increases independence and decreases time spent on bowel management, as well as improves quality of life [55][56][57][58]. Most patients in these studies had received a colostomy; however, some had an ileostomy and a few ended up with both eventually, primarily due to complications.…”
Section: Stomamentioning
confidence: 99%
“…Most patients in these studies had received a colostomy; however, some had an ileostomy and a few ended up with both eventually, primarily due to complications. Preferences of ileostomy vs. colostomy are not particularly discussed nor compared in these studies [55][56][57][58][59]. The decision on stoma formation should be well considered.…”
Section: Stomamentioning
confidence: 99%